Mapping overweight in pregnant women and prematurity: a scope review (Research, Society and Development, 2021)
Introduction: excessive gestacional weght can have implications for health of the pregnant woman and the fetus, and prematurity is important outcome, as despite technologies in neonatal care being increasingly advanced, premature newborns may need hospital care complications, in addition to having a higher risk of death. Objective: To identify and synthesize scientific evidence on the association between obesity during pregnancy and prematurity. Method: This is a scoping review, developed based on the recommendations of the international PRISMA-ScR guide and on the method proposed by the Joanna Briggs Institute, Reviewers Manual 2017. A search was carried out in the established electronic databases. Data collection took place from October/2020 to April/2021. Results: A total of 5140 records were retrieved, 42 studies were selected. Of these, 27 (65.85%) showed a statistically significant association between overweight and prematurity. Low birth weight in pregnant women was also associated with prematurity in 27% of the investigations. Conclusion: Nutritional changes in pregnancy, especially obesity, and also low weight are important elements in determining preterm delivery and should be considered in prenatal care.